(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article is dedicated to the role and significance of Shaken Aimanov`s creative work. Shaken Aimanov is a Kazakh cinema founder, prominent actor, director and art leader. In addition we research works of his young colleagues like M. Begalin, S. Hodzhikov, A. Karsakbaev, Sh. Beisembaev. Key words: kazakh cinema, art, culture, enlightenment, aesthetics.